Analysis of The Correlation Between Mechanical Engineering Research and COVID-19 Situation: Bibliometric Study - Ramadhan, Doni Fajar; Saputra, Nisa Aulia; Sumirat, Uum (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2022)
The rapid spread of the coronavirus has a bad impact on many things, including education, government, the economy. This study was conducted to investigate the development of mechanical engineering research by mapping bibliometrics using the R programming language and VOSviewer. Bibliometric classifications indicate the types of publications, keywords trend, and authors of scientific papers. In this study, data collection was performed from the SCOPUS and dimensions.ai website. This website provides a dataset of scientific papers published in international peer-reviewed journals. The keyword that we used to collected the metadata "mechanical" "engineering" "COVID-19". Based on study that carried out Mechanical research has gradually increased the number of publications in the last ten years even during the COVID-19 pandemic, which indicates this topic is interesting research and continues to increase along with technological developments. Based on keyword analysis, in the era of the COVID-19 pandemic, the keyword that often appears in mechanical engineering research is "e-learning". this indicates that during the covid 19 pandemic, many researchers studied how to teach related to mechanical engineering when schools were still on lockdown. Based on Country Mapping show that USA is the country with the most publications of mechanical engineering research in the COVID-19 pandemic. Europe is the continent that publishes the most with 5 countries in the top 10 rankings of the most publishers. Based on bibliographic mapping from Scopus, the author with the most publications related to mechanical engineering in the COVID-19 pandemic is Kanetaki, Z